PENYULUHAN KARAKTER ANAK BERTEMA “ANAK HEBAT” DI PANTI ASUHAN AGAPE DI PERUMAHAN CIPTA ASRI BATAM - Frengki Marbun; Ray Maharana Simatupang; Imelda Pasaribu; Jalson Nainggolan; Dwi Gladly Marianti (JURNAL BEATITUDES, 2023)
This paper aims to find out and understand the character of children in orphanages where this is a place where underage and disabled children are placed in order to get a better life. With funding from donors who come from various people and various circles. So that there are not a few orphanage foundations that are increasingly developing in terms of facilities, curriculum, business entities, etc. Due to the large number of donations that have come in, residents of the orphanage foundation sometimes misinterpret donations. So that there is an opportunity to take advantage of the conditions in the foundation to get more donations. Seen from the foundation's own foster children, who interpret donations when they are in their position in the foundation. As well as what impact is felt either directly or indirectly from the basic food items and learning equipment. The informants in this study were 5 people consisting of ST3B students. In this study, researchers produced self-confidence in children that they were great. There is interaction from children so as to create happiness.